Preference or ability: Exploring the relations between risk preference, personality, and cognitive abilities. (15th January 2020) - Millroth, Philip; Juslin, Peter; Winman, Anders; Nilsson, Håkan; Lindskog, Marcus
Abstract: Key issues in the behavioral sciences are if there exist stable risk preferences that generalize across domains and if these are best measured by revealed risk preference (RRP) in behavioral decision tasks or by surveys eliciting stated risk preference (SRP). We applied network analysis to data from a representative Swedish sample to investigate the relations between RRP, SRP, personality characteristics, and cognitive abilities, using in total over 70 measurements. The results showed that different measures of RRP were poorly intercorrelated and formed a community together with measures of numerical and cognitive abilities. Measures of SRP were weakly correlated with measures of RRP and identified in a distinctly separate community, along with personality characteristics and gender. The ensuing analyses provided support for a model suggesting that RRPs are contaminated by demands on numerical and cognitive abilities. RRPs may thus suffer from poor construct validity, whereas SRPs may better capture people's everyday risk preferences because they are related to more stable traits.